Integration of Artificial Intelligence in Educational Administration and Human Resources: Conceptual Analysis and Implementation Opportunities in Educational Institutions - Inayah, Dewi; Ali, Moh.; Cahyani, Dewi (Borong Newinera Publisher, 2026)
The development of digital technology has opened up new opportunities in education management. Artificial Intelligence (AI) is emerging as an innovation that enables significant administrative and human resource (HR) management transformations in educational institutions. Through a literature review method, this article discusses how AI can support educational administrative functions ranging from administrative services, data management, to decision-making while strengthening human resource management, including recruitment, training, and performance. The results show that AI integration enables operational efficiency, transparency, and accuracy, as well as the potential to improve the quality of management and performance of human resources. However, there are serious challenges such as infrastructure readiness, digital literacy, as well as ethical and data privacy aspects. For this reason, a digital roadmap, AI literacy training, and internal policies that support smart and ethical implementation in educational institutions are needed.